1998
DOI: 10.1023/a:1018782831217
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Fear and/or anxiety about pain is a useful construct, in both theoretical and clinical terms. This article describes the development and refinement of the Fear of Pain Questionnaire (FPQ), which exists in its most current form as the FPQ-III. Factor analytic refinement resulted in a 30-item FPQ-III which consists of Severe Pain, Minor Pain, and Medical Pain subscales. Internal consistency and test-retest reliability of the FPQ-III were found to be good. Four studies are presented, including normative data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
204
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(230 citation statements)
references
References 32 publications
5
204
1
3
Order By: Relevance
“…From the questionnaire data, participants scored an average of 86.19 (SD ¼ 16.80) on the FPQ and 55.00 (SD ¼ 11.25) on the FPQ-SF. These scores were slightly higher but within one standard deviation of similar healthy and undergraduate samples for both the FPQ (McNeil & Rainwater, 1998;Osman, Breitenstein, Barrios, Gutierrez, & Kopper, 2002) and the FPQ-SF (Carleton & Asmundson, 2009). Participants scored an average of 17.48 (SD ¼ 9.41) on the PCS, which is similar to the average found in other healthy samples (Osman et al, 2000;Sullivan et al, 1995).…”
Section: Descriptive Statisticsmentioning
confidence: 56%
See 1 more Smart Citation
“…From the questionnaire data, participants scored an average of 86.19 (SD ¼ 16.80) on the FPQ and 55.00 (SD ¼ 11.25) on the FPQ-SF. These scores were slightly higher but within one standard deviation of similar healthy and undergraduate samples for both the FPQ (McNeil & Rainwater, 1998;Osman, Breitenstein, Barrios, Gutierrez, & Kopper, 2002) and the FPQ-SF (Carleton & Asmundson, 2009). Participants scored an average of 17.48 (SD ¼ 9.41) on the PCS, which is similar to the average found in other healthy samples (Osman et al, 2000;Sullivan et al, 1995).…”
Section: Descriptive Statisticsmentioning
confidence: 56%
“…The Fear of Pain Questionnaire (FPQ; McNeil & Rainwater, 1998) was used to measure pain-related fear, and has previously been found to have good internal consistency and test-retest reliability (McNeil & Rainwater, 1998). In the current study, the FPQ was found to be reliable (a ¼ 0.925).…”
Section: Questionnairesmentioning
confidence: 99%
“…During the familiarization session, participants completed the informed consent document and six questionnaires consisting of: 1) a Demographic and Pain History Questionnaire, 2) the Pain Catastrophizing Scale (PCS), 71 3) the Fear of Pain-III Scale, 47 4) the Profile of Mood States Questionnaire, 46 5) the Gender Role Expectation of Pain Questionnaire, 60 and 6) the Family Environment Scale. 50 The Demographic and Pain History Questionnaire was used to collect health, pain, and demographic information.…”
Section: Methodsmentioning
confidence: 99%
“…The Brief Pain Inventory - Short Form [37] was used to assess pain severity (subscale α = 0.75 in the present study) and functional interference (subscale α = 0.92 in the present study) prior to treatment, as well as to identify the primary location of pain in the body. The Fear of Pain Questionnaire [38] (α = 0.96 in the present study) was used to measure the extent to which individuals experienced anxiety over the threat of experiencing pain. Participants were also asked to report the duration of their chronic pain.…”
Section: Methodsmentioning
confidence: 99%